During My Time…” (by IMAM Past-Presidents) - Shaharom, Mohamed Hatta; Saim, Lokman; Mas’ud, Ishak; Hassan, Jeffrey Abu (International Journal of Human and Health Sciences (IJHHS), 2023)
May we be protected by Allah the Almighty from self-aggrandisement (ta‘ẓīmun al-dhāti تعظيم الذات), self-delusion (wahmun al-dhātiوهم الذات ) and vanity (ghurūr غرور). Our resolve is to be always on the Path of the Divine instead of the Path of Shaitan. 1. SHIP: Sacrifice (prioritising commitments), Humility (humbling experiences), Intention (solely for Allah), Passion (from the heart). 2. FIMA: Immediate involvement in the international, professional, academic and humanitarian spheres. 3. Islamic Sciences (Diploma, Institut Pengajian Ilmu-Ilmu Islam, Malaysia) and Arabic (Egypt and Malaysia). 4. Islamic Movement: Influence of Ikhwān al-Muslimīn and Jamaat-e-Islami. (Abul A‘la Maududi died in 1979, Yūsuf al-Qaradawi led the funeral prayer at the Lahore Stadium, Pakistan. Leaders, activists and supporters of the Ikhwān were all released by President Anwar Sadat by 1971, only to be harrassed and arrested again by 1979-1981). 5. Academic Administration and Boards of Companies. The politics of academia and intricacies of entrepreneurship. 6. Malay Language and Literature, and DBP: Sastera Tanpa Sains Tiada Kemajuan. Sains Tanpa Sastera Tiada Keanggunan (Literature without science is devoid of advancement. Science without literature is devoid of elegance). “In our time...” describes the struggle and the earnestness of those around us; i.e. family, companions, colleagues and the milieu of professionals and fellow humans who wanted and still want to improve the conditions of the nation and the world. Sorrow Behind the Smiles: Notes on a Humanitarian Journey in Iraq, Kosovo, Afghanistan and Iran. Dewan Bahasa dan Pustaka, Kuala Lumpur 2006. One example of the five books describing international humanitarian missions in Iraq, Kosovo, Afghanistan, Iran, Palestine (Gaza) and Indonesia (Aceh) with IMAM, Mercy Malaysia, MyCARE. As we look to the future with this conference on how we will need to reset, refine, and reform the future of Malaysian Healthcare, we should also look back at how IMAM/PPIM contributed to the current healthcare milieu. We are blessed that 3 of our previous predecessors and presidents of IMAM/PPIM are here today with us to discuss their experiences and challenges in helming IMAM/PPIM during their time in office. We will also eagerly listen to them as we hope they will suggest to us the way forward in the challenges facing our profession and IMAM in the seemingly difficult future facing us. Please do join us in this discourse to better the future of medicine in Malaysia. International Journal of Human and Health Sciences Supplementary Issue: 2023 Page: S10-S11